Stok Ikan Tapah (Wallago leeri) Yang Tertangkap Dengan Menggunakan Alat Tangkap Pengilar (Pot Trap) Di Sungai Sebangau Kota Palangka Raya - Haryuni Haryuni; Anang Najamuddin; Subhan Abror Alhidayat; Firlianty Firlianty (Universitas Lambung Mangkurat, 2019)
This research was conducted to analyze: (1) the composition of Pengilar’s catches on the Sebangau River (2) the parameters of Tapah fish stocks, including size structures and long weight relationship (3) the effectiveness of Pengilar (Pot Trap) fishing gear used in the Sebangau River. This research was conducted in Sebangau River, Sebangau Sub-district, Palangka Raya City, and Limnology Laboratory of Fisheries Department of Palangka Raya University. Based on the research results can be concluded: The composition of fish species caught by using Pengilar (pot trap) fishing gear in Sebangau River during the study of 105 heads consisting of 6 species of fish that is Wallago leeri, Kryptopterus bicirrhis, Anabas testudineus, Mystus nemurus, Pristolepis fasciata, and Helostoma temminckii. It is assumed that the structure of the Wallago leeri from observation frequency and theoretical frequencies tend to consist of only one age group (cohort). Wallago leeri fish has a constant b with a value of W = 2.789 SL and average of 0.958. The value of b indicates that the Wallago leeri fish in the Sebangau River belong to negative allometrics or long increments faster than weight gain, indicating the state of the skinny fish. Lc25% with length of 46,76 cm, Lc75% with length 63.65 cm, and L50% with length of 55,21 cm.